Method for analyzing influence of fly ash addition amount on early strength of sulphoaluminate-based grouting material and fly ash-sulphoaluminate cement grouting material
By analyzing the effect of fly ash addition on the early strength of sulfo-aluminate-based grouting materials, the mass ratio of fly ash to sulfo-aluminate cement was determined to be 10% and 90%, which solved the acidic environment of grouting materials The problem of lower strength decreases improves the mechanical properties and stability of the filling body.
Patent Information
- Application Number
- CN202411727340.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
The existing sulfur aluminate-based grouting materials have decreased strength in an acidic environment and insufficient stability, especially when the fly ash content is high, which affects the mechanical properties and stability of the grouting filler.
By analyzing the effect of fly ash addition on the early strength of sulfa-aluminate-based grouting materials, grouting materials with mass percentages of fly ash and sulfaluminate cement were determined to control fly ash. The particle size distribution and oxide composition are adapted to the acidic environment and form suitable pore structures and hydration products.
Effectively control the changes in hydration strength, improve the mechanical properties and stability of the filling body, and ensure the safety and durability of the project, especially in acidic environments, fly ash-sulfur aluminate grouting filling body The compressive strength and pore structure were optimized.
Smart Images

Figure CN119510235A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of slag filling materials, and specifically relates to an analysis method for the influence of fly ash addition on the early strength of sulphoaluminate-based grouting materials and a fly ash-sulphoaluminate cement grouting material. Background Art
[0002] As shallow coal resources are gradually depleted, coal mining is gradually advancing to deeper areas. However, deep coal tunnels face multiple challenges such as high ground stress, complex geological structures, and broken and soft surrounding rocks. Traditional anchor (cable) net support measures are not effective. If effective measures are not taken, it may lead to safety accidents such as tunnel instability, roof collapse, and spalling, which seriously threaten mine production. Grouting reinforcement is an effective active support method that can improve the performance of surrounding rocks and limit deformation. The performance of grouting fluid is crucial to the reinforcement effect, and it is mainly divided into organic and inorganic types. Organic grouting fluid has excellent performance but high cost and toxicity; inorganic grouting fluid is cheap and harmless, but has poor injectability and difficult to control the setting time. In response to these shortcomings, researchers have developed a cement-based grouting technology system. In practical applications, it is necessary to select appropriate grouting materials according to the characteristics of the surrounding rock of the coal tunnel. For example, large-section soft rock coal tunnels often use a combination of deep and shallow holes for grouting, with ordinary cement used in deep holes and sulphoaluminate cement (CSA) used in shallow holes. However, CSA has too high early expansion, and minerals such as fly ash (FA) need to be added to adjust its performance. In addition, the acidic environment of high-sulfur coal mines may affect the grouting effect. That is, in an acidic environment, the microstructure and strength of FA-CSA grouting materials will be greatly affected. The existing FA-CSA grouting materials will have problems of reduced strength and insufficient stability when used in an acidic environment with a pH below 4. Summary of the invention
[0003] The purpose of the present invention is to provide an analysis method for the effect of fly ash addition on the early strength of sulphoaluminate-based grouting materials and fly ash-sulphoaluminate cement grouting materials to solve the problems raised in the above background technology. The present invention provides the following technical solutions: A method for analyzing the effect of fly ash addition on the early strength of sulphoaluminate-based grouting materials comprises the following steps: S1. Detect the particle size distribution parameters of fly ash and sulphoaluminate cement; S2, mixing an acidic solution with fly ash and sulphoaluminate cement to prepare three kinds of grouting liquids, and then curing to form a filling body; the mass percentages of fly ash and sulphoaluminate cement in the three kinds of grouting liquids are 10% / 90%, 30% / 70% and 50% / 50% respectively; S3. The prepared filling body is subjected to uniaxial compression test, XRD phase test, TG thermal analysis, SEM test and MIP porosity test.
[0004] Preferably, in step S1, the oxide composition of fly ash and sulphoaluminate cement is also analyzed.
[0005] Preferably, three grouting liquids with the same material ratio and deionized water as the liquid medium are used as the control group.
[0006] A fly ash-sulphoaluminate cement grouting material adapted to an acidic environment, wherein the composition of the grouting material is determined by using an analytical method for the influence of fly ash addition on the early strength of the sulphoaluminate-based grouting material; the grouting material comprises fly ash and sulphoaluminate cement; the mass percentages of fly ash and sulphoaluminate cement are 10% and 90% respectively; The particle size distribution parameters D10, D30, D50 and D90 of the fly ash are 7.64 μm, 16.41 μm, 35.14 μm and 107.28 μm respectively; the particle size distribution parameters D10, D30, D50 and D90 of sulphoaluminate cement are 5.92 μm, 11.22 μm, 18.73 μm and 40.15 μm respectively; The mass percentage of CaO in fly ash is 15.385%; The fly ash-sulphoaluminate cement grouting material is applied to an acidic environment with a pH value of 3.5.
[0007] Preferably, the mass percentage of CaO in the sulphoaluminate cement is 54.01%.
[0008] Preferably, the mass percentage of SiO2 in sulphoaluminate cement is 13.61%, and the mass percentage of SiO2 in fly ash is 43.251%.
[0009] Preferably, the mass percentage of Al2O3 in sulphoaluminate cement is 15.38%, and the mass percentage of Al2O3 in fly ash is 25.197%.
[0010] Preferably, the mass percentage of SO3 in sulphoaluminate cement is 10.24%, and the mass percentage of SO3 in fly ash is 4.088%.
[0011] More preferably, the mass percentage of Fe2O3 in sulphoaluminate cement is 2.01%, and the mass percentage of Fe2O3 in fly ash is 8.76%.
[0012] More preferably, the fly ash-sulphoaluminate cement grouting material is configured into a grouting liquid with a liquid-to-solid ratio of 0.5, which is injected into a mold for curing to form a fly ash-sulphoaluminate cement grouting filling body; the curing temperature is 20±1°C, and the curing humidity is 93±3%.
[0013] More preferably, the uniaxial compressive strength of the fly ash-sulphoaluminate cement grouting filling body is 11.05 MPa after hydration for 1 day, and the strength is 26.73 MPa after hydration for 7 days.
[0014] The beneficial effects of the present invention compared with the prior art are as follows: 1. In fly ash-sulphoaluminate cement grouting filling, the change of hydration strength can be effectively controlled by controlling the fly ash content, avoiding the strength loss caused by high fly ash content. This helps to improve the mechanical properties and stability of the filling body and ensure the safety and durability of the project.
[0015] 2. In an acidic environment, the pore structure and compressive strength of the fly ash-sulphoaluminate grouting filling body will be affected. The present invention pays attention to the negative effects of the acidic environment on the cementitious system and takes corresponding measures to adjust it in time. At the same time, for the filling body exposed to the acidic environment for a long time, the fly ash-sulphoaluminate cement grouting material of the present invention has stronger stability.
[0016] 3. The present invention can better understand and control the mechanical properties of the filling body by establishing a relationship between the compressive strength and the pore parameters. In particular, the porosity determined by the volume of mesopores and macropores has an effect on the compressive strength, which provides an important reference for design and construction and helps to optimize the structure and performance of the filling body.
[0017] 4. The present invention adjusts the mass ratio of fly ash to sulphoaluminate cement and conducts comparative tests in an acidic environment and a neutral environment with a pH of 3.5. The study adopts methods such as uniaxial compressive test, XRD phase analysis, TG thermal analysis, SEM micromorphology observation and MIP pore test to comprehensively analyze the strength development, hydration product formation and microstructural evolution of grouting materials under different conditions. The results show that the acidic environment promotes the strength development of fly ash-sulphoaluminate cement grouting filling body, especially when the fly ash content is high. This strength improvement is directly related to the increase in AFt and C-(A)-SH content. The acidic environment is conducive to the recrystallization of AH and the growth of AFt, while increasing the solubility of high-calcium fly ash and promoting the pozzolanic reaction. In addition, the acidic environment and the addition of high-calcium fly ash optimize the pore structure of the grouting filling body, forming more mesopores and macropores, which is conducive to the improvement of long-term strength and durability. This study provides new technical approaches and innovative ideas for the application of sulphoaluminate-based grouting materials in special environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The present invention is further described in detail below in conjunction with the accompanying drawings: Figure 1 is the particle size distribution of fly ash and sulphoaluminate cement in the examples; Figure 2The XRD phases of fly ash and sulphoaluminate cement in the examples; Figure 3 is the uniaxial compressive strength of the fly ash-sulphoaluminate cement grouting filling body in the embodiment after hydration for 1 day, 3 days and 7 days; Figure 4 This is one of the phase diagrams of the fly ash-sulphoaluminate cement grouting filling body in the embodiment when it is hydrated for 1 day, 3 days and 7 days; Figure 5 The second phase diagram of the fly ash-sulphoaluminate cement grouting filling body in the embodiment when it is hydrated for 1 day, 3 days and 7 days; Figure 6 The third phase diagram of the fly ash-sulphoaluminate cement grouting filling body in the embodiment when it is hydrated for 1 day, 3 days and 7 days; Figure 7 The DTG curve of the fly ash-sulphoaluminate cement grouting filling body in the embodiment when it is hydrated for 7 days; Figure 8 is the pore distribution parameter of the fly ash-sulphoaluminate cement grouting filling body when it is hydrated for 7 days in the embodiment; Fig. 9 is a graph showing the relationship between the strength of the grouting filling body and the pore size distribution parameters in the embodiment; Fig.10 It is the Aft exposed to the gelling system in the examples. DETAILED DESCRIPTION
[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail in conjunction with the embodiments and the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical solutions of the present invention are described in detail below in conjunction with the embodiments and the accompanying drawings, but the scope of protection is not limited thereto.
[0020] See also Figures 1 to 10 This embodiment proposes an analysis method for the effect of fly ash addition on the early strength of sulphoaluminate-based grouting materials and fly ash-sulphoaluminate cement grouting materials; it is used to analyze the effect of fly ash addition on the early strength of sulphoaluminate-based grouting materials, and provide new technical approaches and innovative ideas for the application of sulphoaluminate-based grouting materials in special environments. The method includes the following steps: Step 1: The solid raw materials involved in this embodiment mainly include fly ash and sulphoaluminate cement, and their particle size distribution curve is as follows: Figure 1As shown. It can be seen that the particle size distribution parameters D10, D30, D50 and D90 of fly ash are 7.64μm, 16.41μm, 35.14μm and 107.28μm, respectively, while the particle size distribution parameters D10, D30, D50 and D90 of sulphoaluminate cement are 5.92μm, 11.22μm, 18.73μm and 40.15μm, respectively. The difference in particle size distribution between the two is conducive to the increase of the packing density of the solid material system, thereby improving its solidification performance in terms of physical stacking angle. In addition, the oxide composition results of fly ash and sulphoaluminate cement are shown in Table 1. The main oxides (content > 1%) of the two are SiO2, Al2O3, CaO, Fe2O3 and SO3, etc., and the CaO content in fly ash is 15.385%, indicating that it is a high-calcium fly ash with good pozzolanic activity. As Figure 2 The XRD phase analysis of fly ash and sulphoaluminate cement is shown. The results show that the main mineral phases of the sulphoaluminate cement are calcium sulphoaluminate, tricalcium silicate, dicalcium silicate, gypsum and calcium carbonate, etc.; the main mineral phases of fly ash are mullite, quartz and magnetite, etc., among which the phase peak of 2θ∈15°~30° presents a slightly raised "steamed bun shape" as a whole, indicating that the fly ash contains a certain amount of amorphous phase, which is also the reason for the high volcanic ash activity of high calcium fly ash. In addition to the above solid materials, the materials used in this embodiment also include concentrated sulfuric acid and deionized water.
[0021] Step 2: After the prepared grouting liquid is pumped into the surrounding rock of the coal tunnel, it quickly contacts with the seepage water in the fissures. The entire solidification process of the grouting filling material is in the seepage water environment. Therefore, in order to simplify the test, this embodiment directly uses a dilute sulfuric acid solution with a pH of 3.5 to fully mix with the solid material. The mass percentages of fly ash and sulphoaluminate cement are 10% / 90%, 30% / 70% and 50% / 50%, respectively, and the corresponding sample numbers are FC 1-3.5 , FC 2-3.5 and FC 3-3.5 ; In order to analyze the effect of acidic environment on the hydration process of grouting filling, a control group with the same material ratio and deionized water (pH=7) as the liquid medium was added. The corresponding sample numbers are FC 1-7 , FC 2-7 and FC 3-7 The liquid-to-solid ratio of all new slurry samples was 0.5. The detailed test plan is shown in Table 2.
[0022] Step 3: Prepare the grouting liquid according to the test plan, pour a part of the fresh slurry into a cylindrical plastic mold with a size of Ф50mm×100mm, prepare 5 samples for each ratio, seal the upper mouth of the mold with plastic wrap, and place it in a curing box for curing at a temperature of 20±1°C and a humidity of 93±3%. After reaching the curing age, perform a uniaxial compression test. Pour another part of the fresh slurry into a 10ml centrifuge tube, prepare 9 samples for each ratio, and after reaching the curing age, use isopropanol to terminate the hydration, dry in a drying oven at 45°C, grind and put into a label bag for microscopic characterization testing.
[0023] Step 4, Uniaxial Compression Test (UCS): After the grouting filling reaches 1 day, 3 days and 7 days, the test blocks are subjected to uniaxial compression test. The pressure test machine uses Humboldt HM-5030 test machine, the maximum loading load is 50kN, the loading speed during the test is 1mm / min, and the displacement loading method is used. Before the test, both ends of the test block are kept as flat as possible, and vaseline is applied to reduce the influence of end friction. At least three test blocks are tested and the average value is taken as the final compressive strength value.
[0024] Step 5, XRD phase test: Panalytical X'pert Prodiffractometer was used for XRD test, with copper target as target material, continuous scanning mode, scanning step length of 0.026°, scanning speed of 5° / min, and qualitative analysis sample scanning for 9 minutes.
[0025] Step 6, TG thermal analysis: Use STA409PC isothermal calorimeter (Germany) to perform semi-quantitative analysis on certain specific hydration products. Take about 30 mg of sample powder each time and put it into an alumina crucible, and heat it from room temperature to 1000°C in a nitrogen environment at a heating rate of 15°C / min. From this, the amount of chemically bound water (CBW) and portlandite (CH) in the hydration product can be calculated as: ; ; Among them, M 50 , M 400 and M 550 are the remaining mass of the sample when the temperature rises to 50°C, 400°C and 550°C respectively.
[0026] Step 7, SEM test: Before the microscopic morphology test, the sample was first subjected to gold spraying to increase its conductivity. The JEOL JSM-7800F scanning electron microscope was used for observation, with an acceleration voltage of 10~15kV and a working distance of 8~15mm.
[0027] Step 8, MIP pore test: According to ASTM D4404-18 standard, the pore distribution of the grouting solidified filling body is measured using Micromeritics' AutoPore IV 9500 mercury intrusion instrument produced in the United States. The maximum working pressure of the mercury intrusion instrument is 414MPa, and the pore size test range is 3nm~1000μm. After the test block has undergone uniaxial compressive strength test, take a sample away from the failure surface, and it is necessary to ensure that the sample has no obvious cracks. Soak it in isopropanol, stop hydration for 12h, and then dry it in a vacuum dryer to constant weight. Prepare the sample into small pieces less than 10mm×10mm×10mm and put it into a closed dryer for testing. The results of the pore test are affected by many factors, such as sample size, pretreatment technology, surface tension and contact angle during mercury intrusion, among which the relationship between mercury pressure and pore size can be expressed as: in conclusion: (1) Uniaxial compressive strength Figure 3 The figure shows the uniaxial compressive strength of the fly ash-sulphoaluminate cement grouting filling body at 1 day, 3 days and 7 days of hydration time. Obviously, with the increase of fly ash addition ratio, the strength of the grouting filling body at each age has decreased significantly. This is because the hydration activity of high-calcium fly ash is much lower than that of sulphoaluminate cement. The higher amount of fly ash reduces the hydration products of the cementitious system, resulting in a decrease in the density of the microstructure of the grouting filling body, a weakening of the strengthening benefit of the cementitious material on the solid particle skeleton, and a certain extent, the prolongation of the setting time of the sample. Figure 3 As shown in (a), the uniaxial compressive strength of the sample with 10% fly ash addition after hydration for 1 day was 11.05MPa and 13.41MPa, respectively, while after hydration for 7 days, its strength only reached 26.73MPa and 34.02MPa; the uniaxial compressive strength of the sample with 50% fly ash addition after hydration for 1 day was only 4.06MPa and 5.14MPa, respectively, while after hydration for 7 days, its strength only reached 10.05MPa and 16.93MPa. Comparing the grouting filling bodies with 10% and 50% fly ash addition, it can be seen that the strength decreased by 63.26% and 61.67% after hydration for 1 day, and decreased by 62.41% and 50.23% after hydration for 7 days. It can be seen that when grouting reinforcement is carried out, it is necessary to fully consider the requirements of the grouting reinforcement area for cementing properties. While meeting the requirements of grouting reinforcement properties, adding an appropriate amount of fly ash can reduce the cost of grouting reinforcement.
[0028] In addition, it can be observed that under the influence of the acidic environment, the strength of the grouting filling body of each ratio has decreased, but the degree of decrease varies slightly due to the hydration time and the proportion of fly ash added. For example, when the grouting filling body was hydrated for 1 day, 3 days and 7 days, the acidic environment caused the strength of the sample with 10% fly ash addition to decrease by 17.60%, 19.36% and 21.42% respectively; the strength of the sample with 30% fly ash addition decreased by 22.46%, 19.97% and 30.71% respectively; the strength of the sample with 50% fly ash addition decreased by 21.01%, 28.89% and 39.45% respectively. The strength loss of the grouting filling body with 50% fly ash addition was large after hydration for 7 days, which indicates that the hydration reaction of cement clinker is temporarily dominant in the early stage of the cementitious system and is less affected by the acidic environment; with the extension of hydration time, the active components of high calcium fly ash gradually dissolved and released in large quantities to participate in the hydration reaction, and its process was greatly affected by the acidic environment. The hydration of fly ash causes the cementitious system to produce a part of CASH, which enhances the acid resistance. However, the high amount of fly ash greatly reduces the production of cementitious substances. The acidic environment destroys C-(A)-SH and further weakens the strength gain of the solid skeleton. The decrease in its uniaxial compressive strength is naturally greater.
[0029] (2) XRD phase analysis To further study the microstructural evolution of fly ash-sulphoaluminate-based grouting materials under acidic environment, the mineral phases of samples hydrated for 1, 3 and 7 days were analyzed. Figure 4 Of Figure 6 The most active component in the cementitious system of fly ash-sulfoaluminate-based grouting materials is calcium sulfoaluminate. When the grouting material comes into contact with water, calcium sulfoaluminate rapidly hydrates to produce a product with volume expansion, ettringite (AFt, Ca6Al2(SO4)3(OH) 12 ·26H2O), which is also the main reason for its rapid setting in the early stage of hydration. As shown in Figure 4 (a) and (b), the main phase peaks of AFt are located at 2θ<9.091°> and 2θ<15.784°>. When the fly ash-sulfoaluminate grouting material is in an acidic environment, the phase peak intensity of AFt is significantly weakened when the hydration time is 1 day and 3 days. This is mainly due to the inhibition of the dissolution of active Al in fly ash under acidic conditions, and the hydration of calcium sulfoaluminate is also inhibited. When the hydration time reaches 7 days, the peak intensity of the AFt phase of the grouting material sample in the acidic environment has only a slight attenuation, which indicates that SO4 2- The gain of ion concentration on AFt generation gradually increased. When the hydration time of the grouting material sample increased from 1 day to 7 days, the AFt peak intensity showed a trend of first increasing and then decreasing, regardless of whether it was in an acidic environment or not. This indicates that the SO4 2-As the ion concentration decreased, part of the AFt phase was transformed into AFm (AFm, Ca4Al2O6(SO4)·14H2O). Since the AFm phase is amorphous, it was not identified by XRD. When the addition of fly ash increased from 10% to 50%, the AFt peak of the corresponding sample also showed a similar change pattern, which will not be repeated here. In addition, according to the content of portlandite (CH) in the cementitious system and SO4 2- ion concentration, a certain amount of aluminum gel (AH3) is also generated. Similar to AFm, it is also amorphous and cannot be identified by XRD.
[0030] Monocarbonate aluminate (M c The phase peak (2θ<11.681°>) of Ca4Al2O6(CO3)·11H2O) did not appear when the pulverized coal content in the grouting volume was 10% and 30% and the hydration time was 1 day. This is because the CO3 2- The ion concentration is low; for the grouting material sample with pulverized coal content of 50%, a weak M c The phase peak shows that fly ash has priority in carbon adsorption and solidification, which increases the CO3 2- When the curing time continued to increase to 3 days and 7 days, M c The phase peaks continued to increase, which was attributed to the continuous adsorption of CO2 and CO3 in the air by the gel system. 2- Ion replacement of SO4 in AFm 2- Ion formation M c . Semi-carbonate aluminate (H c ,Ca4Al2O6(CO3) 0.5 The phase peaks of (OH)·11.5H2O) (2θ<10.781°> and 2θ<21.661°>) are Figure 5 and Figure 6 It can be observed in (c) to (f) that it is mainly composed of M c Phase transition usually depends on the molar ratio of CO3 / (CO3+2OH). 2-3.5 After hydration for 1 day, CO3 2- The ion concentration is low, OH - Replace M c Part of CO3 2- Transformed into H c , and as the gel adsorbs more CO2, CO3 2- The increase in ion concentration increases the molar ratio of CO3 / (CO3+2OH), which promotes H c Phase transformation to M c For FC 3-7 For the sample, H cphase, mainly due to the strong alkalinity of the gelling system, which leads to a decrease in the molar ratio of CO3 / (CO3+2OH), OH - Replace M c Part of CO3 2- Transformed into H c .
[0031] The peak intensity of the calcium hydroxide (CH, Ca(OH)2, 2θ<34.102°>) phase decreases with the increase of fly ash addition ratio and curing age. This is mainly because the initial pozzolanic reaction of fly ash consumes part of CH, and CH continuously adsorbs CO2 to form calcium carbonate (Calcite, CaCO3, 2θ<29.455°>) with the increase of curing time. However, Figure 4 Of Figure 6 As shown in Figure 2, the peak strength of calcium carbonate of all samples basically decreases with the increase of curing age, which is consistent with the above c The generation and consumption of Calcite are related. In addition, due to the effect of the acidic environment, the background peak intensity of the sample at Calcite is slightly weak, which also shows the erosion of C-(A)-SH (2θ<27.199°~30.043°>) by the acidic environment, which will reduce the solid skeleton strength of the solidified filling body. Phase peaks such as dicalcium silicate (C2S, Ca2SiO4), tricalcium silicate (C3S, Ca3SiO5) and quartz (SiO2) also appear in the cementitious system, which are mainly minerals and inert minerals that have not undergone hydration reaction in the cementitious system.
[0032] (3) TG thermal analysis The mass percentage change of fly ash-sulphoaluminate cement grouting filling body with hydration for 7 days with temperature was tested and the TG curve was recorded. The DTG curve was obtained by taking the first-order derivative as shown in Figure 7 The DTG peaks at 50°C to 150°C mainly correspond to the thermal decomposition and dehydroxylation of AFt and C-(A)-SH, and the DTG peaks at 150°C to 250°C mainly correspond to the thermal decomposition and dehydroxylation of H c and M c The thermal decomposition and dehydroxylation of FC is the main reason for the thermal decomposition and dehydroxylation of CH, while the DTG peak at 400°C~550°C mainly corresponds to the thermal decomposition and dehydroxylation of CH. Correspondingly, the amounts of CBW and CH can be calculated as shown in Table 3. 1-3.5 and F 1-7 The AFt / C-(A)-SH decomposition peak intensity of the grouting filling body is the highest, indicating that it contains the most hydration products such as AFt and C-(A)-SH after hydration for 7 days; the filling body solidifies to form a denser pore structure and a strengthened solid skeleton structure, which makes the filling body have a higher compressive strength (such as Figure 3 (a)). In addition, FC 1-3.5 and F1-7 Grouting filling body in H c / M c The decomposition peaks of CH and CH have higher intensity values, which indicates that the gel system contains more H c / M c and CH, which is consistent with the XRD phase results. c / M c The decomposition peaks of CH and CH decreased, which is related to the relatively low hydration activity of fly ash, and the pozzolanic reaction consumes a large amount of CH, so the CH content is naturally low. In addition, the acidic environment also has a certain effect on the hydration reaction of fly ash-sulphoaluminate cement. For the 10% fly ash-sulphoaluminate cement grouting filling body, the acidic environment with a pH of 3.5 caused the cementitious system to reduce the hydration products of chemically bound water by 0.67%, and the amount of CH was reduced by 0.14%; for 30% fly ash and 50% fly ash additions, the corresponding values were 0.71% / 0.58% and 2.03% / 1.37%, respectively. This shows that the attenuation effect of the acidic environment on the cementitious system shows an increasing trend, which is consistent with the attenuation trend of the uniaxial strength of the grouting filling body in the acidic environment ( Figure 3 Sulphoaluminate cement has good resistance to hydrochloric acid and sulfuric acid erosion, and its strength loss rate is lower in acidic environment.
[0033] (4) Microscopic pore analysis Figure 8 (a) is the microscopic pore distribution of fly ash-sulfoaluminate cement grouting filling body after hydration for 7 days under the influence of acidic environment. According to the literature, the pores are classified as follows: 0~20nm belongs to micropores; 20~1000nm belongs to mesopores; and larger than 1000nm belongs to macropores. It can be seen that the difference in micropore volume of grouting filling bodies of different proportions is not large, and the difference in pore distribution is mainly reflected in mesopores and macropores. FC 3-3.5 It has a large macropore volume, a sparse pore structure, and a small amount of early hydration products ( Figure 7 ), its uniaxial compressive strength value is the lowest (10.25MPa). In addition, the pore size corresponding to the most concentrated distribution of pore size values is defined as the threshold pore size (Cr) of the grouting filling body, as shown in Figure 8 (b) shows the porosity of the grouting filling body of each ratio, FC 1-3.5 / 7 , FC 2-3.5 / 7 and FC 3-3.5 / 7 The corresponding porosity values of the samples are 30.26% / 28.14%, 35.64% / 32.19% and 39.45% / 35.97% respectively. 3-3.5Except for the sample with Cr = 1436 nm, the threshold pore sizes of the other grouting filling bodies are all in the medium pore range; 1-7 It has the smallest threshold pore size of 351 nm and the smallest porosity (28.14%), indicating that its pore structure is dense, and its early hydration products are more ( Figure 7 ), resulting in the maximum compressive strength (39.02MPa). The relationship between the strength of the grouting filling and the microscopic pore parameters is established, such as Fig. 9 As shown in Figure 2, the linear fitting correlation parameter R between the filling strength and the threshold pore size is 2 is 0.639, while the linear fitting correlation parameter R between filling strength and porosity is 2 It is 0.935, which shows that the volume of filled mesopores and macropores determines the compressive strength value.
[0034] The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be regarded as belonging to the present invention and the scope of patent protection determined by the submitted claims.
Claims
1. An analytical method for the effect of fly ash addition on the early strength of sulphoaluminate-based grouting materials, characterized in that: The following steps are involved: S1. Detect the particle size distribution parameters of fly ash and sulphoaluminate cement; S2, mixing an acidic solution with fly ash and sulphoaluminate cement to prepare three kinds of grouting liquids, and then curing to form a filling body; the mass percentages of fly ash and sulphoaluminate cement in the three kinds of grouting liquids are 10% / 90%, 30% / 70% and 50% / 50% respectively; S3. The prepared filling body is subjected to uniaxial compression test, XRD phase test, TG thermal analysis, SEM test and MIP porosity test.
2. The method for analyzing the effect of fly ash addition on the early strength of sulphoaluminate-based grouting materials according to claim 1, characterized in that: In step S1, the oxide compositions of fly ash and sulphoaluminate cement are also analyzed.
3. The method for analyzing the effect of fly ash addition on early strength of sulphoaluminate-based grouting materials according to claim 1, characterized in that: Three grouting solutions with the same material ratio and deionized water as the liquid medium were used as the control group.
4. A fly ash-sulphoaluminate cement grouting material, characterized in that: The composition of the grouting material is determined by using an analytical method for the effect of fly ash addition on the early strength of the sulphoaluminate-based grouting material; the composition of the grouting material is composed of fly ash and sulphoaluminate cement; the mass percentages of fly ash and sulphoaluminate cement are 10% and 90% respectively; The particle size distribution parameters D10, D30, D50 and D90 of the fly ash are 7.64 μm, 16.41 μm, 35.14 μm and 107.28 μm respectively; the particle size distribution parameters D10, D30, D50 and D90 of sulphoaluminate cement are 5.92 μm, 11.22 μm, 18.73 μm and 40.15 μm respectively; The mass percentage of CaO in fly ash is 15.385%; The fly ash-sulphoaluminate cement grouting material is applied to an acidic environment with a pH value of 3.
5.
5. A fly ash-sulphoaluminate cement grouting material according to claim 4, characterized in that: The mass percentage of CaO in sulphoaluminate cement is 54.01%.
6. A fly ash-sulphoaluminate cement grouting material according to claim 5, characterized in that: The mass percentage of SiO2 in sulphoaluminate cement is 13.61%, and the mass percentage of SiO2 in fly ash is 43.251%.
7. A fly ash-sulphoaluminate cement grouting material according to claim 6, characterized in that: The mass percentage of Al2O3 in sulphoaluminate cement is 15.38%, and the mass percentage of Al2O3 in fly ash is 25.197%.
8. The fly ash-sulphoaluminate cement grouting material according to claim 7, characterized in that: The mass percentage of SO3 in sulphoaluminate cement is 10.24%, and the mass percentage of SO3 in fly ash is 4.088%.
9. A fly ash-sulphoaluminate cement grouting material according to claim 8, characterized in that: The fly ash-sulphoaluminate cement grouting material is configured into a grouting liquid with a liquid-to-solid ratio of 0.5, which is injected into a mold for curing to form a fly ash-sulphoaluminate cement grouting filling body; the curing temperature is 20±1°C, and the curing humidity is 93±3%.
10. The fly ash-sulphoaluminate cement grouting material according to claim 9, characterized in that: The uniaxial compressive strength of the fly ash-sulphoaluminate cement grouting filling body after hydration for 1 day is 11.05 MPa, and the strength after hydration for 7 days is 26.73 MPa.
Citation Information
Cited By
Method for calculating ion locking capacity of concentrated salt mine well water mixed coal-based filling material
CN121347705A